2010
DOI: 10.22146/ijc.21498
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS OF COPPER OXIDE NANO PARTICLES BY USING Phormidium cyanobacterium

Abstract: In this paper, we report a suitable method for extracellular synthesis of copper oxide nano particles by using Phormidium cyanobacterium. We hypothesize that synthesis of copper oxide nano particles is believed to occur by extracellular hydrolysis of the cationic copper by certain metal chelating anionic proteins/reductase secreted by bacteria under simple experimental conditions like aerobic environment, neutral pH and room temperature. Proteins not only reduce Cu (II) into copper oxide nano particles (CONPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 2 publications
3
30
0
Order By: Relevance
“…As sodium borohydride (NaBH 4 ) concentration increased cuprous oxides formation was favored. These results suggested the formation of Cu 2 O and CuO in colloidal solution, which was in agreement with results previously reported [43,[62][63][64]. One explanation for these results is the high activity of copper NPs which are obtained during the synthesis.…”
Section: Effect Of Sodium Borohydride Nabhsupporting
confidence: 92%
“…As sodium borohydride (NaBH 4 ) concentration increased cuprous oxides formation was favored. These results suggested the formation of Cu 2 O and CuO in colloidal solution, which was in agreement with results previously reported [43,[62][63][64]. One explanation for these results is the high activity of copper NPs which are obtained during the synthesis.…”
Section: Effect Of Sodium Borohydride Nabhsupporting
confidence: 92%
“…This study sought the biogenic synthesis of CuO-NPs by P. mirabilis strain 10B which was clearly apparent visually by the variations in the color of bacterial biomass and the ambient aqueous solution from pale green to brown or faint black as indicated in Figure 1(a). In a parallel control experiment, no distinctly remarkable changes were noticed, suggesting the onset of biotransformation via reduction of metal ions to an oxide form of Cu-NPs by reducing agent (bacteria) in the growth medium [24]. It is noteworthy that such changing in the reaction solution color arises from excitation of surface plasmon resonance (SPR) or interband transitions in the metal NPs, which are a characteristic feature for any particles with a metallic nature.…”
Section: Biosynthesis and Characterization Of Npsmentioning
confidence: 99%
“…(1) Intracellular CuO-NPs. Usually, TEM technique was employed to provide an insight on the shape, size, and Journal of Nanomaterials location of NP synthesis and also protein-coating NPs [24]. Figures 6 and 7 depicted the representative TEM micrographs of CuO-NPs and their bionanofactory during the stationary growth phase.…”
Section: Microstructure Analysis (Tem)mentioning
confidence: 99%
“…A recent study revealed that nano-scale materials exhibit unique electronic and optical properties, which are unlike those in their bulk state [1]. Metallic nanoparticles have attracted attention of many researchers, because of the local field enhancement at nano interfaces, which is beneficial for a number of applications, from sensors to nonlinear optics [2].…”
Section: Introductionmentioning
confidence: 99%